2006
DOI: 10.1038/nature04892
|View full text |Cite
|
Sign up to set email alerts
|

The association of GRB 060218 with a supernova and the evolution of the shock wave

Abstract: Although the link between long gamma-ray bursts (GRBs) and supernovae has been established, hitherto there have been no observations of the beginning of a supernova explosion and its intimate link to a GRB. In particular, we do not know how the jet that defines a gamma-ray burst emerges from the star's surface, nor how a GRB progenitor explodes. Here we report observations of the relatively nearby GRB 060218 (ref. 5) and its connection to supernova SN 2006aj (ref. 6). In addition to the classical non-thermal e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
984
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(1,051 citation statements)
references
References 24 publications
49
984
2
5
Order By: Relevance
“…gamma-ray bursts with peak energies below approximately 50 keV. Observational evidence suggests that the radio and high-energy emission is due to the breakout of a relativistic shock from the surrounding massive wind of the progenitor star [2,[15][16][17][18]. Apart from SN 2003dh (and possibly SN 2012bz), the best-studied supernovae related to gamma-ray bursts are all members of this class.…”
Section: Supernovae Associated With Long-duration Gamma-ray Burstsmentioning
confidence: 99%
“…gamma-ray bursts with peak energies below approximately 50 keV. Observational evidence suggests that the radio and high-energy emission is due to the breakout of a relativistic shock from the surrounding massive wind of the progenitor star [2,[15][16][17][18]. Apart from SN 2003dh (and possibly SN 2012bz), the best-studied supernovae related to gamma-ray bursts are all members of this class.…”
Section: Supernovae Associated With Long-duration Gamma-ray Burstsmentioning
confidence: 99%
“…The existence of an additional blackbody component in the prompt X-ray spectrum of GRB 060218 (Campana et al 2006) and GRB 100316D (Starling et al 2011) has been reported. The blackbody temperature is stable in the range of 0.1-0.2 keV up to several hundreds of seconds after the trigger, and then, decreases to < 0.01 keV.…”
Section: Additional Blackbody Component In X-ray Spectrummentioning
confidence: 94%
“…While GRB 060218 and GRB 100316D show a duration of several thousands of seconds (Campana et al 2006;Starling et al 2011), SN-GRBs with a duration of a several tens to hundreds of seconds are also common. Although the durations of GRB 060218 and GRB 100316D are exceptionally long, the rest of the sample is well within the duration distribution of typical long GRBs (Figure 2).…”
Section: Durationsmentioning
confidence: 99%
“…One then might get a long X-ray flash visible at large angles. An example might be XRF 060218 (Campana et al 2006). …”
Section: Discussionmentioning
confidence: 99%